STRATEGI KOMUNIKASI DINAS PERHUBUNGAN DALAM MENINGKATKAN MINAT PENGGUNA ANGKUTAN TRANS METRO DI PEKANBARU - Putra, Evandi Julian; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Trans Metro Pekanbaru is starting to operate on June 18, 2009. Trans Metro Pekanbaru is a mass public transportation system in the city of Pekanbaru, is a solution to congestion gradually and programmed for the community. Implementation of mass public transportation system (SAUM) Trans Metro Pekanbaru often received criticism and complaints from the public. Trans Metro has not been optimized to position itself as a mass public transport that is safe, comfortable, scheduled, reliable and sustainable. Related to that the Department of Transportation of Pekanbaru city to do communication strategy that aims to increase public interest using Trans Metro Pekanbaru. This research was conducted to find out the strategy of communicator, media strategy, supporting and inhibiting factors, and communication model by City Transportation Department Pekanbaru.This research uses descriptive qualitative research method. The subjects involved in this study were determined based on purposive and Insidental technique consisting of seven informants, two informants from Transportation Department of Pekanbaru and five informants of Trans Metro Pekanbaru users. Data collection techniques include interviews, observation and documentation. Data analysis techniques using interactive data model Miles and Huberman with the examination of the validity of the data is done by using the extension technique of participation and triangulation. The result of the research shows that Transportation Department uses communication strategy such as communicator strategy where communicator of Forest Service in conveying information has credibility, knowledge, and skill. The media used by the Department of Transportation is the face-to-face media or directly, the mass media used are electronic media, online media, and non-mass media that is stickers and brochures. Supporting factors are facilities and infrastructure and economic tariff, inhibiting factors are lack of bus stop, bus delay, lack of awareness of society, and lack of bus special lane based on communications strategy done by City Transportation Department Pekanbaru.Keywords: Communication Strategy, Transportation, and Interest